Nucleotide sequence of pS194, a streptomycin-resistance plasmid from Staphylococcus aureus. - Projan, S J (1988)
pS194 is a naturally occurring Staphylococcus aureus plasmid encoding streptomycin resistance. The plasmid has a copy number of about 25 per cell, and belongs to the inc5 incompatibility group. The nucleotide sequence of pS194 has been determined and consists of 4397 base pairs including four open reading frames potentially encoding proteins of greater than 100 amino acids. All four of these reading frames are on the same coding strand. The first reading frame, repE, encodes a 38 kd protein specifically required for pS194 replication. The second open reading frame, str, encodes a 34 kd polypeptide required for streptomycin resistance, probably a streptomycin adenylyltransferase. The third potential polypeptide, rlx, would be 37 kd and is probably required for relaxation complex formation and plasmid mobilization by conjugative plasmids. The fourth, orfD, overlapping the rlx reading frame, is potentially 27 kd, and may also be involved in mobilization.